Clinical Study on Comparative Effect of Khandamalaki Rasayana and Gudakushmandaka Rasayana in Urdwaga Amlapitta - Hosur Chaitrika; Belavadi S.N (International Journal of Ayurveda and Pharma Research, 2021)
Amlapitta is one of the most common disorder of the Annavaha Srotas (digestive System). Improper food intake, changed diet pattern and mental stress are the main contributing factors for disease manifestation. Among two types of Amlapitta, Urdwaga Amlapitta is most common in clinical practice. Amlodgara (sour belching), Urodaha (burning sensation), Hrillasa (nausea) are the major symptoms of it. The disease can be co-related with the hyperacidity, hyperchlorhydria or gastritis. Complications caused by the regular use of Modern medicine for the disease encouraged the current study. Clinical trial of Khanadamalaki Rasayana and Gudakushmandaka Rasayana is conducted on 40 subjects of Urdwaga Amlapitta in two divided groups i.e., Group A and Group B. Single Blind Study Design was applied for the study. Patients were selected from OPD of DGM Ayurvedic Medical College and Hospital for respective trial. Criteria of assessment are set aside on the basis of relief in the signs and symptoms of subjective parameter of Urdwaga Amlapitta. Among 40 patients 8 patients got moderate relief and 32 patients got complete relief from the Symptoms by the treatment. Conclusively the treatment was satisfactorily effective in the patients. The criteria of the assessment and Statistical analysis reveal that Gudakushmandaka Rasayana is more effective than Khandamalaki Rasayana in treating the Urdwaga Amlapitta. The drugs used in this study are having the properties of Pittashamana and Rasayana, So these are helpful in curing the disease along with correcting the Agni and general condition of the patient.